Is Less Invasive Surfactant Administration Better than INtubation-SURfactant-Extubation for Prophylactic Surfactant Replacement Therapy? - Hyung-Joon Joo; Gyu Hong Shim (Korean Society of Neonatology, 2022)
Purpose The study aimed to examine whether prophylactic surfactant replacement therapy (SRT) with less invasive surfactant administration (LISA) by tracheal catheterization in a group of spontaneously breathing preterm infants would improve clinical outcomes compared to prophylactic SRT with the INtubation-SURfactantExtubation (INSURE) method. Methods We compared 20 spontaneously breathing preterm infants, 25 to 29 weeks of gestation or with a birth weight of less than 1,250 g, treated with prophylactic SRT using a gastric tube (LISA group), to the 20 spontaneously breathing preterm infants matched by gestational age and birth weight, managed with prophylactic SRT via the INSURE method (INSURE group, historical control). Results The LISA group had lower rates of mechanical ventilation (MV) 72 hours after birth (P=0.019) and at any time (P=0.025), lower frequency of bradycardia during SRT (P=0.031), and lower median duration of MV than the INSURE group (P=0.038). In multivariate analysis, the LISA method was associated with a significantly lower likelihood of receiving invasive ventilation during hospitalization (odds ratio [OR], 0.029; 95% confidence interval [CI], 0.001 to 0.938; P=0.046) and a decreased frequency of bradycardia during SRT (OR, 0.020; 95% CI, 0.001 to 0.535; P=0.020) as compared to the INSURE method. Conclusion Prophylactic SRT using LISA via tracheal catheterization in preterm infants may significantly reduce exposure to MV during hospitalization and bradycardia during surfactant administration.